2007
DOI: 10.1101/gr.6548207
|View full text |Cite
|
Sign up to set email alerts
|

Direct linkage of mitochondrial genome variation to risk factors for type 2 diabetes in conplastic strains

Abstract: Recently, the relationship of mitochondrial DNA (mtDNA) variants to metabolic risk factors for diabetes and other common diseases has begun to attract increasing attention. However, progress in this area has been limited because (1) the phenotypic effects of variation in the mitochondrial genome are difficult to isolate owing to confounding variation in the nuclear genome, imprinting phenomena, and environmental factors; and (2) few animal models have been available for directly investigating the effects of mt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
66
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(72 citation statements)
references
References 30 publications
6
66
0
Order By: Relevance
“…Another limitation of mitochondrial association studies is that they are potentially confounded by the nuclear background as there is significant cross-talk between the two systems. Some of the most convincing evidence for a role of mtDNA in metabolic phenotypes comes from studies of mice with identical nuclear genomes, but different mitochondrial genomes [11]. In this regard, twin studies may prove to be a valuable resource in trying to uncover the role of mitochondria in disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another limitation of mitochondrial association studies is that they are potentially confounded by the nuclear background as there is significant cross-talk between the two systems. Some of the most convincing evidence for a role of mtDNA in metabolic phenotypes comes from studies of mice with identical nuclear genomes, but different mitochondrial genomes [11]. In this regard, twin studies may prove to be a valuable resource in trying to uncover the role of mitochondria in disease.…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondria may also play a role in the metabolic syndrome, as evidenced by a mutation in the tRNA ILE gene (also known as MT-TI) at nucleotide position 4,291 causing hypertension, hypercholesterolaemia and hypomagnesaemia [10]. A recent study using rats with identical nuclear genomes but differing mitochondria showed that mitochondrial variants have a direct effect on a number of metabolic phenotypes, including triacylglycerol levels [11].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, while fibrogenesis/fibrinolysis genes are predicted to be strong candidates to influence liver fibrosis, only one report has shown a link between transforming growth factor-β 1 (TGF-β 1) and angiotensinogen polymorphisms and obesity induced liver fibrosis [141]. Lastly, it should be mentioned that an association between naturally occurring variations in the mitochondrial genome and conditions of the cardiometabolic syndrome has been proposed [142,143]. Recently, Pravenec et al [142] using conplastic rat strains with the same nuclear genome but dissimilar mitochondrial genomes encoding oxidative phosphorylation proteins of differing amino acid composition showed differences in glucose and glycogen metabolism; two risk factors for type 2 diabetes.…”
Section: Genetic Factors Determining the Pathobiology Of Fatty Liver mentioning
confidence: 99%
“…Lastly, it should be mentioned that an association between naturally occurring variations in the mitochondrial genome and conditions of the cardiometabolic syndrome has been proposed [142,143]. Recently, Pravenec et al [142] using conplastic rat strains with the same nuclear genome but dissimilar mitochondrial genomes encoding oxidative phosphorylation proteins of differing amino acid composition showed differences in glucose and glycogen metabolism; two risk factors for type 2 diabetes. Whether mtDNA variants are linked to risk factors associated with steatosis, hepatitis, and fibrosis/ cirrhosis is a stimulating concept and one that clearly requires further study.…”
Section: Genetic Factors Determining the Pathobiology Of Fatty Liver mentioning
confidence: 99%
“…The amount of mitochondrial DNA (mtDNA) was estimated as described earlier. 21 The results in pioglitazone treated rats were expressed as fold increases relative to the mean normalized expression level of the control rats that was arbitrarily defined as 1.…”
Section: Biochemical Analysesmentioning
confidence: 99%